1996
DOI: 10.1007/bf00018709
|View full text |Cite
|
Sign up to set email alerts
|

Effect of growth on reproduction in the freshwater amphipod, Hyalella azteca (Saussure)

Abstract: A gradient in H. azteca growth was created by reducing food ration . .Tests were initiated with neonates (<48 h old) and the effects of an altered food ration on survival and growth were examined after 10 and 49 days . Growth rates decreased significantly with reduced food ration (10 day growth rates ranged from 1 .2 tg d -1 in the highest feeding regime to 0 .5 tg d -1 in lowest feeding regime) . Survival after 10 days was not affected by ration, ranging from 86 to 96% . A growth rate of 1 .2 jig d -1 at day … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
31
0
5

Year Published

1998
1998
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 28 publications
5
31
0
5
Order By: Relevance
“…4). Other investigators have reported a similar degree of variability in reproduction of H. azteca within a narrow range of length or weight, with stronger correlations observed over wider ranges [26,30,48,49]. The degree of correlation between growth and reproduction may also be dependent on the strain of H. azteca evaluated [26,50].…”
Section: Relationship Between Growth and Reproduction Endpointsmentioning
confidence: 72%
“…4). Other investigators have reported a similar degree of variability in reproduction of H. azteca within a narrow range of length or weight, with stronger correlations observed over wider ranges [26,30,48,49]. The degree of correlation between growth and reproduction may also be dependent on the strain of H. azteca evaluated [26,50].…”
Section: Relationship Between Growth and Reproduction Endpointsmentioning
confidence: 72%
“…The gender of the adult H. azteca was not determined prior to distribution and therefore it is possible that some buckets contained only males or only females, which would result in no reproduction. Also, as reported by Moore and Farrar [14], buckets housing a high ratio of males compared with females would produce very few offspring.…”
Section: Discussionmentioning
confidence: 64%
“…The CCIW strain had, on average, a greater number of adults per breeding bucket which likely increased the chances of successful pairing [14]. In addition, the CCIW H. azteca were cultured in water (SAM-5S) that was optimized for their specific strain by Borgmann [10].…”
Section: Discussionmentioning
confidence: 99%
“…En cuanto a la abundancia de Hyalella azteca, diversos autores han mostrado que tanto el crecimiento como el desarrollo de los anfipodos es afectado por varios factores ambientales, resaltando de manera especial la temperatura (Bovee, 1950;Cooper, 1965;De March, 1977), el fotoperiodo (Pilgrim y Burt, 1993) y la calidad del alimento (Hargrave, 1970;Moore y Farrar, 1996;Wellborn, 1994); ademas estos organismos por su tamaño se encuentran en sitios que ofertan protección contra sus depredadores (peces, aves, insectos acuáticos y anfibios), habitando principalmente entre las macrófitas de la zona litoral, algas bentónicas y el microbentos (Mathias, 1971;Alcocer et al, 2002;Peralta, 2006). Al parecer, las condiciones de los lagos fueron adecuadas, registrando a la especie en los dos periodos de estudio con relativa abundancia en ambos lagos.…”
Section: Discussionunclassified